Changes in intraocular pressure during strabismus surgery - Yoo, Chungkwon; Chang, Mun Hee; Song, Jong-Suk; Kim, Seung-Hyun (Canadian Journal of Ophthalmology, 2010)
Objective: To determine whether the alterations in intraocular pressure (IOP) after cutting off a lateral rectus muscle during exotropia surgery could reflect the degree of muscle contracture. Design: Prospective study. Participants: Sixty eyes of 31 patients that had undergone lateral rectus recession surgery for correction of exotropia. Methods: IOP was measured usingaTono-pen XL before and after detaching lateral rectus muscles during the surgery. The changes in IOP were measured and their correlations with age, duration of disease, intermittency of exotropia, amount of exodeviation, laterality of the deviated eye, and tendon width of the muscle operated on were analyzed. Results: The mean baseline IOP was 16.3 (SD2.2) mm Hgwhen measured 5 minutes after tracheal intubation and showed a significant decline to 13.5 (SD 2.8) mm Hgwhen measured immediately before detachment of a muscle. However, the IOP decline over this period of preparation for muscle detachment was not correlated with any clinical variable tested. The mean IOP also showed a significant reduction, to 10.8 (SD 2.3) mm Hg, immediately after the muscles were cutoff the globe. The peridetachment IOP reduction was positively correlated with constant exodeviation ( p < 0.001), whereas there was no significant correlation with age, duration of exotropia, or tendon width. Conclusions: The changes in IOP seen after detaching an extraocular muscle during strabismus surgery may serve as a surrogate parameter to reflect the muscle contracture. Objet: Déterminer si les altérations de la pression intraoculaire (PIO) après la coupure du muscle droit latéral pendant la chirurgie de l’exotropie pourraient en refléter le degré de contracture. Nature: Étude prospective. Participants: Soixante yeux (31 patients) qui avaient subi une récession du droit latéral pour corriger l’exotropie. Methodes: La mesure de la PIO a été prise avec Tono-pen XL avant et après le détachement du muscle droit latéral pendant la chirurgie. Les changements de pression ont été mesurés et l’on a analysé leurs corrélations avec l’âge, la durée de la maladie, l’intermittence de l’exotropie, le degré d’exophorie, la latéralité de la déviation oculaire et la largeur du tendon du muscle opéré. Résultats: En moyenne, la PIO de base etait de 16,3 (ÉT 2,2) mm Hg lorsque la mesure était prise 5 minutes après l’intubation de la trachée et montrait une réduction significative de 13,5 (ÉT 2,8) mm Hg quand la mesure était prise immédiatement avant le détachement du muscle. Toutefois, la baisse de la PIO pendant cette période de préparation pour le détachement du muscle n’était en corrélation avec aucune variable clinique testée. La PIO moyenne a aussi montre une baisse significative, à 10,8 (ÉT 2,3) mm Hg, immédiatement après la coupure des muscles du globe. La réduction de la PIO lors du péridétachement était positivement en corrĺation avec l’exodéviation constante ( p < 0,001), alors qu’il n’y avait pas de corrélation significative avec l’âge, la durée de l’exotropie ou la largeur du tendon. Conclusions: Le changement de la PIO après le détachement extraoculaire du muscle pendant la chirurgie du strabisme peut servir de substitut pour refléter la contracture du muscle.